Peran Guru IPS dalam Meningkatkan Minat Belajar Siswa Kelas VIII di SMP Negeri 1 Srengat Kabupaten Blitar - Luluk Baikuna; Jani Jani (Badan Penerbit STIEPARI Press, 2025)
This study is motivated by the decline in students' learning interest, particularly in Social Studies (IPS) subjects. Teachers play a crucial role in guiding and supporting students to enhance their motivation and interest in learning. The objective of this research is to describe the role of Social Studies teachers as facilitators and motivators, as well as to identify the supporting and inhibiting factors in increasing the learning interest of eighth-grade students at SMP Negeri 1 Srengat, Blitar Regency, in the 2024/2025 academic year. This research employs a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings indicate that the teacher's role as a facilitator is reflected in accompanying students during the learning process and providing guidance according to their abilities. As a motivator, the teacher encourages students by emphasizing the importance of learning and showing motivational videos to inspire them. Supporting factors include adequate facilities and infrastructure, and good collaboration among teachers. Inhibiting factors consist of inefficient teaching hours, students' learning difficulties due to psychological, family, and peer influences, as well as environmental factors such as negative peer groups and low literacy engagement among students.